The Influence of Servant Leadership, Emotional Quotient, and Work Stress on Organizational Citizenship Behavior (A Study on Employees at the Meruya Selatan Sub-District Office) - Sherin Desriani; Mochamad Soelton (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the influence of Servant Leadership, Emotional Quotient, and Work Stress on Organizational Citizenship Behavior among employees at the Meruya Selatan Village Office. The population in this study consists of all Public Facilities and Infrastructure Handling Officers at the Meruya Selatan Village Office. The sample in this study includes the entire population, totaling 82 people, using the saturated sample method. This study applies a quantitative approach with a causal research design. Data were collected through the distribution of questionnaires, while data analysis was conducted using Partial Least Squares (PLS) with the help of SmartPLS software. The results show that Servant Leadership has a positive and significant effect on Organizational Citizenship Behavior. Emotional Quotient also has a positive and significant effect on Organizational Citizenship Behavior. Meanwhile, Work Stress has a negative and significant effect on Organizational Citizenship Behavior. These findings indicate the importance of strengthening Servant Leadership, Emotional Quotient, and managing Work Stress to improve employees' Organizational Citizenship Behavior.